The activating NKG2D ligand MHC class I-related chain A transfers from target cells to NK cells in a manner that allows functional consequences. - McCann, F; Eissmann, P; Onfelt, B; Leung, R; Davis, D (2007)
Recently, it has become apparent that surface proteins commonly transfer between immune cells in contact. Inhibitory receptors and ligands exchange between cells during NK cell surveillance and we report here that NK cells also acquire activating ligands from target cells. Specifically, the stress-inducible activating ligand for NKG2D, MHC class I-related chain A (MICA), transferred to NK cells upon conjugation with MICA-expressing target cells. Acquisition of MICA from target cells was dependent on cell contact and occurred after accumulation of MICA at the immunological synapse. Moreover, transfer of MICA was facilitated by specific molecular recognition via NKG2D and augmented by Src kinase signaling. Importantly, MICA associated with its new host NK cell membrane in an orientation that allowed engagement with NKG2D in trans and indeed could down-regulate NKG2D in subsequent homotypic interactions with other NK cells. MICA captured from target cells could subsequently transfer between NK cells and, more importantly, NK cell degranulation was triggered in such NK cell-NK cell interactions. Thus, NK cells can influence other NK cells with proteins acquired from target cells and our data specifically suggest that NK cells could lyse other NK cells upon recognition of activating ligands acquired from target cells. This mechanism could constitute an important function for immunoregulation of NK cell activity.